2015
DOI: 10.1021/acs.jafc.5b02105
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in Plant-Based Dietary Supplements: Hidden Health Risk for Consumers

Abstract: Mycotoxin contamination of dietary supplements represents a possible risk for human health, especially in the case of products intended for people suffering from certain health conditions. The aim of this study was to assess the extent of this problem based on analyses of a wide set of herbal-based dietary supplements intended for various purposes: (i) treatment of liver diseases (milk thistle); (ii) reduction of menopause effects (red clover, flax seed, and soy); and (iii) preparations for general health supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 21 publications
4
84
0
2
Order By: Relevance
“…The FS available on the EU market are produced worldwide and some are manufactured by European companies. Although a number of reports have exposed the doubtful quality of selected FS produced outside the EU (Dolan et al 2003;Rzymski et al 2015a;Veprikova et al 2015;Rao et al 2017), there still remained a need to screen the European formulas. The present study is a comprehensive assessment of EU-manufactured multiingredient supplements based on minerals and vitamins sold in Polish pharmacies as regards their bioavailability, and levels of essential and toxic elements.…”
Section: Discussionmentioning
confidence: 99%
“…The FS available on the EU market are produced worldwide and some are manufactured by European companies. Although a number of reports have exposed the doubtful quality of selected FS produced outside the EU (Dolan et al 2003;Rzymski et al 2015a;Veprikova et al 2015;Rao et al 2017), there still remained a need to screen the European formulas. The present study is a comprehensive assessment of EU-manufactured multiingredient supplements based on minerals and vitamins sold in Polish pharmacies as regards their bioavailability, and levels of essential and toxic elements.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these data were reported by only one country (the Czech Republic). Veprikova et al (2015) reported similarly high concentrations of T2 and HT2 in dietary supplements based on various herbs or plants collected from the Czech and US retail markets, and it is possible that a part of their data might have also been submitted to EFSA.…”
Section: Occurrence Data On Foodmentioning
confidence: 99%
“…V případě doplňků stravy však zůstává otázkou efektivita i bezpeč-nost těchto preparátů, např. kvůli vysokému obsahu mykotoxinů, které byly v takových přípravcích objeveny [2]. Registrovaná léčiva obsahující extrakt standardizovaný na obsah silymarinu se pře-depisují při léčbě jaterních onemocnění, např.…”
Section: úVodunclassified